Wernicke’s encephalopathy- a case report - Adhikari, Baikuntha Raj; Sapkota, N; Gautam, R; Basnet, M; Koirala, P; Limbu, S (Journal of BP Koirala Institute of Health Sciences, 2018)
Wernicke's encephalopathy is a neuropsychiatric disorder characterized by acute onset, nystagmus and oculomotor abnormalities, and a confusional state. Chronic alcohol intake is still the most common reason. Wernicke's encephalopathy, if not recognized and treated, can become irreversible. Common findings in Magnetic Resonance Imaging (MRI) include: symmetric T2 Weighted Image (T2) hyperintensities in peri-aqueductal gray matter, dorsal medial thalamus and mammillary bodies. This case highlights neurological deficits, persistent memory and disorientation.Journal of BP Koirala Institute of Health Sciences, Vol. 1, No. 1, 2018, page: 78-81